Optimization of extraction conditions of phytochemical compounds and anti-gout activity of euphorbia hirta L. (Ara Tanah) using response surface methodology and liquid chromatography-mass spectrometry (LC-MS) analysis - Abu Bakar, Fazleen Izzany; Abu Bakar, Mohd Fadzelly; Abdullah, Norazlin; Endrini, Susi; Fatmawati, Sri (Hindawi, 2020)
Gout is a common disease affected most of the people due to the elevation of uric acid in the blood. Flavonoid and phenolic compounds are reported to exert the anti-gout activity of medicinal plants. Hence, this study aimed at optimizing the extraction conditions of phenolic and flavonoid compounds as well as the anti-gout (xanthine oxidase inhibitory activity) in vitro of Euphorbia hirta using response surface methodology (RSM). /e plant part used was the whole plant excluding roots. /e effects of three independent variables (extraction time, X1; extraction temperature, X2; and solid-to-liquid ratio, X3) on three response variables (total flavonoid content, Y1; total phenolic content, Y2; and xanthine oxidase inhibitory activity, Y3) were determined using central composite design (CCD) while phytochemical profiling of the extracts was determined by liquid chromatography-mass spectrometry (LC-MS). Quadratic models produced a satisfactory fitting of the experimental data with regard to total flavonoid content (r2 = 0.9407, p < 0.0001), total phenolic content (r2 = 0.9383, p < 0.0001), and xanthine oxidase inhibitory activity (r2 = 0.9794, p < 0.0001). /e best extraction conditions observed for total flavonoid content, total phenolic content, and xanthine oxidase inhibitory activity were at a temperature of 79.07°C for 17.42 min with solid-to-liquid ratio of 1 : 20 g/ml. /e optimum values for total flavonoid, total phenolic, and xanthine oxidase inhibitory activity were 67.56 mg RE/g, 155.21 mg GAE/g, and 91.42%, respectively. /e main phytochemical compounds in the optimized E. hirta extract are neochlorogenic acid, quercetin-3β-D-glucoside, syringic acid, caffeic acid, ellagic acid, astragalin, afzelin, and quercetin. As conclusion, this study clearly demonstrated the best conditions to obtain higher xanthine oxidase inhibitory activity and phytochemical compounds which can be further used for the development of anti-gout agents.